2014
DOI: 10.1038/srep05601
|View full text |Cite
|
Sign up to set email alerts
|

TR-FRET Assays of Huntingtin Protein Fragments Reveal Temperature and PolyQ Length-Dependent Conformational Changes

Abstract: Time-Resolved Fluorescence Resonance Energy Transfer (TR-FRET) technology is a widely used immunoassay that enables high-throughput quantitative measurements of proteins of interest. One of the well established examples is the TR-FRET assay for mutant huntingtin protein (HTT), which is the major cause of the neurodegenerative Huntington's disease (HD). To measure the mutant HTT protein, the published assays utilize a polyQ antibody, MW1, paired with HTT N-terminal antibodies. MW1 has much higher apparent affin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 23 publications
(40 reference statements)
8
39
0
Order By: Relevance
“…If 3B5H10 recognizes a toxic conformation present only in expanded polyQ, then unlike MW1, it should not bind to short polyQ repeats. In contrast with some previous results [9], but consistent with other results [10, 11], we found that both MW1 and 3B5H10 IgGs bound in a similar manner to huntingtin exon 1 fusion proteins, each capable of binding to huntingtin exon 1 proteins containing both normal and expanded polyQ repeats. Both IgGs bound to huntingtin exon 1 proteins in a polyQ-dependent manner, with a progressively more intense signal with increased polyQ length.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…If 3B5H10 recognizes a toxic conformation present only in expanded polyQ, then unlike MW1, it should not bind to short polyQ repeats. In contrast with some previous results [9], but consistent with other results [10, 11], we found that both MW1 and 3B5H10 IgGs bound in a similar manner to huntingtin exon 1 fusion proteins, each capable of binding to huntingtin exon 1 proteins containing both normal and expanded polyQ repeats. Both IgGs bound to huntingtin exon 1 proteins in a polyQ-dependent manner, with a progressively more intense signal with increased polyQ length.…”
Section: Resultssupporting
confidence: 89%
“…This model postulates that both normal and expanded polyQ tracts in the preaggregation state are random-coil structures, with expanded polyQ repeats containing more epitopes recognized by antibodies or other binding proteins than normal polyQ tracts [3]. Several lines of evidence, reported here and in previous publications [6, 11], have shown that 3B5H10 and MW1 IgGs can bind to a normal polyQ repeat, demonstrating that neither antibody preferentially recognizes a novel structure formed by expanded polyQ, but instead both recognize a short stretch of polyQ. This conclusion is in contrast to other studies suggesting that 3B5H10 bound preferentially to expanded polyQ repeats of mutant huntingtin according to a ‘structural toxic threshold’ model, in which a conformational transition occurs in the polyQ repeat of huntingtin exon 1 protein at the pathologic threshold (>37Q) [9].…”
Section: Discussionsupporting
confidence: 55%
“…No such differences were observed with the control 2B7/4C9 TR-FRET immunoassay (Fig. 5C), consistent with the requirement to interrogate the polyQ region with one of the two antibody pairs 11, 12 . Collectively, these data indicate that the 2B7/MW1 TR-FRET based conformational immunoassay can effectively detect the conformational constraint imposed by polyQ expansion on HTT in human cellular models of HD, either under conditions where HTT is overexpressed or where it is expressed at endogenous levels from the relevant genomic locus.
Figure 5The 2B7/MW1 conformational immunoassay detects mHTT conformation in lysates of immortalized control and HD human fibroblasts (obtained from heterozygous HD donors).
…”
Section: Resultssupporting
confidence: 76%
“…Httex1 is composed of three domains: an N-terminal region (N17); a central polyQ region; and a C-terminal Pro-rich domain (PRD) (17). Several studies have found that Httex1 loses its conformational flexibility when the Q-length expands above disease threshold (17)(18)(19), and the reduced flexibility resulting from expanded polyQ has been suggested as a poten- tial contributor to Htt toxicity (9). The N17 region plays a crucial role in the structural changes and altered cellular behavior conferred by polyQ expansion.…”
mentioning
confidence: 99%
“…Although N17 and N17-polyQ interactions are critical for mitigating HD progression, the structural basis for this mitigation is only partly understood. Recent studies show that Httex1 as well as other N-terminal Htt fragments have a partial ␣-helical structure that is augmented by increased Q-length as well as decreased temperature (18,19). Two recent NMR analyses, one performed on an Httex1-based peptide fragment containing 17 Gln residues and the other mostly performed on Httex1 containing 16 Gln residues, found ␣-helical propensity in the N17 region that extends into the polyQ region (23,24).…”
mentioning
confidence: 99%